Newborn Care Practice and Associated Factors among Mothers of One-Month-Old Infants in Southwest Ethiopia - Amanuel Nuramo Sakelo; Nega Assefa; Lemessa Oljira; Zebene Mekonnen Assefa (International Journal of Pediatrics)
Newborn care refers to the care that is provided to the baby from birth to one-month-old by a caregiver or by the mothers including thermal care, hygienic care, cord care, eye care, breastfeeding, immunization, and identification of newborn danger signs. According to Ethiopian Demographic and Health Survey (EDHS) 2016, the neonatal mortality rate was 29 deaths per 1000 live births, and the postneonatal mortality rate was 19 deaths per 1000 live births with neonates contributing 48 deaths per 1000 of the infant mortality. Neonatal mortality accounts for approximately two-thirds of all infant mortality worldwide. Objective. The objective of this study was to assess newborn care practice and associated factors among mothers with babies of one-month-old in Hossana town, Southern Nations, Nationalities, and Peoples’ Region, Ethiopia, 2018. Methods. A community-based cross-sectional study was conducted among randomly selected 422 mothers with babies of one-month-old in Hossana town, southwest Ethiopia. The data were entered to EpiData 3.1 and exported to Statistical Package for the Social Sciences (SPSS) version 22. Bivariate and multivariate analyses were applied, and frequencies and odds ratios were calculated to determine the prevalence and associated factors, respectively. Results. In this study, 31% of participants had good newborn care practice based on three composite variables such as 84% who have done early breastfeeding initiation, 32.9% who have done safe cord care, and 30.6% who have done thermal care. Educational status of the mother’s, primary (AOR=2.80, 95% CI: 1.027-7.637), secondary (AOR=2.596, 95% CI: 0.921-7.316), and college and above (AOR=3.63, 95% CI: 1.056-12.492); mothers who practiced handwashing (hygiene) before touching a newborn (AOR=2.552, 95% CI: 1.092-5.963); and mothers who had good knowledge on newborn care practice (AOR=15.638, 95% CI: 3.599-67.943) were significantly associated with newborn care practice. Conclusion and Recommendation. The present study indicated that the level of comprehensive newborn care practice was unsatisfactory; all responsible bodies were giving attention and intervene on the predictors to improve newborn care practice and provide health education regarding newborn care practice. Education level, health education (counseling) on hygiene, and knowledge of mother on newborn care practice were independent predictors of newborn care practice.